(untitled) (Revista Lusófona de Educação, 2025)
This exploratory and descriptive study aimed to analyse the challenges faced by teachers and the pedagogical strategies they adopt when addressing controversial issues in the classroom. Controversial issues are complex social constructs that mobilise different worldviews and are immersed in contexts of high social sensitivity and intense emotional charge. The administration of questionnaires to 86 teachers from various educational levels made it possible to identify: the most frequently addressed and considered relevant issues; the factors that motivate the choice of controversial issues; the main challenges encountered; and the pedagogical strategies employed to deal with them. The results reveal that, although teachers value the educational potential of controversial issues, a range of challenges causes discomfort in carrying out the work they believe should be undertaken. On the other hand, they demonstrate the development of pedagogical strategies for addressing controversial issues that converge on the common goal of shaping critical, conscious, and respectful citizens. The data analysis also revealed the need for greater investment in professional development programmes based on strategies for facilitating dialogue, mediating conflicts, and creating safe learning environments for the expression of diverse viewpoints. Keywords: controversial issues; citizenship education; teacher training; critical thinking.